100 hours of astronomy at the Mexican northern border - Villicaña-Pedraza, I. (2019)
The International Astronomical Union (IAU) encourages inclusivity1 and information technology presents tools that can make astronomy accessible to all. By using social media, our outreach proposal intends to inspire the next generation of astronomers. By using apps and social media combined with traditional talks, interaction between the public and researchers can be facilitated, and a more diverse audience can be reached, in line with the IAU’s mission to build a wide astronomy-literate community in a costeffective way.